Correlating impairment of quality of life and severity of melasma: A cross-sectional study of 141 patients - Preeti Kothari; Yugal Kishor Sharma; Milind A Patvekar; Aayush Gupta (Wolters Kluwer Medknow Publications, 2018)
Background: The relationship between impaired quality of life (QoL) due to melasma and its clinical severity remains equivocal despite several studies. Aim: The aim was to study the correlation, if any, between the clinical severity and the impairment in QOL due to melasma. Methods: This cross-sectional, questionnaire-based study was conducted on a cohort of 141 patients of melasma attending the outpatient department of our referral hospital. A physician measured the severity of melasma using the melasma area and severity index (MASI), while melasma-related QoL (MELASQOL) score was calculated utilizing the validated Hindi version of the MELASQOL questionnaire filled by the patients. Correlations of these two scores with each other and with components of the demographic data were attempted using the Statistical Package for the Social Sciences, version 20. Results: Significantly greater impairment in QoL was found in patients with a history of prior use of triple combination therapy and in patients with hirsutism and/or polycystic ovarian disease. The severity of melasma was found to be significantly higher in patients with a history of recurrence and tobacco chewing. Limitations: The sample size could have been larger. Ultrasonography could have been carried out in all cases of hirsutism. Conclusion: The severity of melasma does not correlate with the impairment in QoL.